Ti3C2TX MXene Nanolaminates with Ionic Additives for Enhanced Gas-Sensing Performance - Lee, Juyun; Kang, Yun Chan; Koo, Chong Min; Kim, Seon Joon (American Chemical Society, 2022)
MXene nanomaterials have shown outstanding gas-sensing performance at room temperature because of their electrical conductivity and high-density surface functional groups. The sensing properties of MXenes are largely governed by surface adsorption and interlayer diffusion. In light of this sensing mechanism, surface alkalization and ion intercalation have been shown to enhance the gas-sensing performance of MXenes. However, a simple and reliable method for realizing this is still lacking. Here, we present an efficient method to enhance the sensing performance of Ti3C2Tx MXene sensors while retaining their native uniform laminate structure. We show that by adding a controlled amount of alkaline ionic additives, the density of hydroxyl surface groups and intercalated metal ions can be increased inside the thin film structure, which cannot be achieved using acidic or neutral ionic additives with similar elemental compositions. In terms of a signal-to-noise ratio (SNR), Ti3C2Tx mixed with potassium hydroxide was 20 times more sensitive than pristine Ti3C2Tx toward ethanol vapor, thus demonstrating its high sensitivity. In addition, a very high SNR of 700 was achieved toward 100 ppm ammonia gas, which is one of the highest ever reported.